2014 European Elections: European Political Parties, Presidential Candidates and the Pan-eu Campaign. Issue 1 (June 2013) - Sasmatzoglou, Kostas
The 2014 European elections will be the first to take place under the Lisbon Treaty. The nomination of presidential candidates by European political parties will personalise the campaign and will trigger the interest of the European public.